EDUCATIONAL LEADERSHIP AND COMPETENCIES: A PROPOSAL FOR TEACHER EDUCATION. - Gorrochotegui Martell, Alfredo (Atenas, 2012)
This paper offers proposal for the development of teaching skills, evidenced in daily action through competences or qualities in three dimensions: "knowledge," "know-how," and "being and living." The first dimension describes studiousness, the second, the capacity to transmit order and stimulate learning, and the third, respect for students, teamwork and self-criticism Questions for reflection and practical suggestions for improvement are presented in each area for teachers to consider. All of these skills come together to form leadership, shaping teachers who are capable of being "guides", thus showing through their work a way to be genuinely educational.